A review and agenda for examining how technology-driven changes at work will impact workplace mental health and employee well-being. Issue 3 (August 2020) - Johnson, Anya; Dey, Shanta; Nguyen, Helena; Groth, Markus; Joyce, Sadhbh; Tan, Leona; Glozier, Nicholas; Harvey, Samuel B
The mental health and well-being of employees is an increasingly important issue, both in terms of the financial costs to the Australian economy and human costs to society. This review examines two major technology-driven trends in the workplace and presents evidence for their impact on mental health, both positive and negative. First, we consider how we work, with a focus on changes which have been driven by automation and advanced technology in the workplace. Next, we consider where and when we work, with a focus on flexible work arrangements afforded by changes in telecommunication technology. Finally, we look forward with a critical lens to examine the implications for future research and for industry, government and education. JEL Classification:I31